Measuring epistemologies in science learning and teaching: A systematic review of the literature. Issue 5 (28th May 2021) - Lee, Silvia Wen‐Yu; Luan, Hui; Lee, Min‐Hsien; Chang, Hsin‐Yi; Liang, Jyh‐Chong; Lee, Yuan‐Hsuan; Lin, Tzung‐Jin; Wu, An‐Hsuan; Chiu, Ying‐Ju; Tsai, Chin‐Chung
Abstract: Promoting understanding of the epistemologies of science has long been the primary objective in science education, and can be viewed as a form of science learning outcome. Many studies have attempted to understand learners' conceptions of epistemology in science from various perspectives and methods; however, no recent reviews have focused on the measurement of various constructs and variables of epistemologies of science. The main purpose of this review study is to understand how these epistemologies in science teaching and learning were measured, and to provide an overview of recent developments with respect to the measurement issue in the epistemology of science. We searched for articles that were published between 2010 and 2019 and retained 225 eligible studies passing all review criteria for inclusion in this review. Major constructs of epistemologies of science emerging from the studies include epistemic beliefs and views, nature of science, epistemic emotions, epistemic metacognition, epistemic practices, and epistemic resources. These constructs were further categorized into personal, productive, and practical epistemologies. Among these studies, most of the quantitative studies used questionnaires for measuring personal epistemologies, while only a few utilized close‐ended items. The majority of the studies adopting qualitative methods investigated personal epistemologies as well. Nevertheless, among studies of practical epistemologies, more studies adopted qualitative methods than quantitative methods. We summarize the characteristics and psychometric properties of the most frequently used quantitative research instruments. Examples of qualitative data collection and data analyses are provided. Relationships between epistemologies and science learning outcomes are discussed, and suggestions are made for future directions.